Cochlea-inspired tonotopic resonators. (March 2023) - Dal Poggetto, Vinícius F.; Bosia, Federico; Urban, David; Beoletto, Paolo H.; Torgersen, Jan; Pugno, Nicola M.; Gliozzi, Antonio S.
Graphical abstract: Highlights: A novel design for a tonotopic resonator based on a cochlea-inspired spiral is proposed. The structure can discriminate the frequency content of elastic waves without the use of sub-wavelength resonators. The concept is validated using numerical simulations and experimental measurements using a 3D printed structure. The tonotopic behavior can also be inverted for appropriate parameter ranges and boundary conditions. The obtained tonotopic features can be used in applications such as non-destructive testing. Abstract: The cochlea has long been the subject of investigation in various research fields due to its intriguing spiral architecture and unique sensing characteristics. One of its most interesting features is tonotopy, the ability to sense acoustic waves at different spatial locations based on their frequency content. In this work, we propose a novel design for a tonotopic resonator, based on a cochlea-inspired spiral, which can discriminate the frequency content of elastic waves without the use of sub-wavelength resonators. The structure is the result of an optimization process to obtain a uniform distribution of displacement maxima along its centreline for frequencies spanning nearly two-decades, while maintaining a compact design. Numerical simulations are performed to demonstrate the concept and experimental measurements to validate it on a 3D printed structure. The resulting frequency-dependent distribution is also shown to be a viable means to discriminate signals with various frequency components. We also show that for appropriate parameter ranges, the tonotopic behaviour can be inverted, i.e., lower frequencies can be made to concentrate in narrower regions, as happens in the real cochlea. The harnessed tonotopic features can be used as a fundamental principle to design structures with applications in areas such as non-destructive testing and vibration attenuation.